Delayed drug hypersensitivity reactions: How p-i transforms pharmacology into immunology - Werner J. Pichler (Allergology International)
Delayed drug hypersensitivity reactions (dDHRs) are iatrogenic diseases, which are mostly due to non-covalent interactions of a drug with the immune receptors HLA and/or TCR causing T-cell activation. This is also known as pharmacological interaction with immune receptors or p-i. P-i activation differs from classical antigen-driven immune reactions: a) drug binding induces structural changes in TCR-HLA proteins which make them look like allo-like TCR-HLA-complexes, able to elicit allo-like stimulations of T cells with cytotoxicity and IFNγ production, notably without the involvement of innate immunity; b) drug binding to TCR and/or HLA can increase the affinity of TCR-HLA interactions, which may affect signaling and IL-5 production by CD4+ T cells, and thus contribute to eosinophilia commonly found in dDHRs or induce oligoclonal T cell expansions; c) Both, antigen and p-i stimulations can induce eosinophil- or neutrophil-rich inflammations; but these stimulations should be distinguished as their underlying mechanism and development differ; and d) p-i stimulation can – like graft versus host reactions – result in long-lasting T-cell activations, which can lead to viremia, occasional autoimmunity, or a new syndrome characterized by multiple drug hypersensitivity (MDH).In summary, dDHRs are not allergic reactions but represent peculiar T-cell activations, similar to allo-like stimulations. Understanding and considering the p-i mechanism is needed for preventive measures and optimal treatments of dDHR. In addition, it may help to understand TCR signaling, alloreactivity, and may even open a new way of specific immune stimulations.